Fire performance of non-loadbearing light steel framing walls – numerical and simple calculation methods - Piloto, P.A.G. (2020)
Light steel frame and prefabricated panels are widely used in non-loadbearing walls, with direct application to steel framed buildings. Such panels consist of channel steel sections (studs and tracks) with gypsum plasterboard layers attached to the flanges on the outside and use insulation material in the cavities. The fire resistance is usually provided by one or more layers of panels and also by the insulation material.